REPRESENTASI PEMBERITAAN PEMULANGAN EKS GAFATAR RIAU DI SURAT KABAR RIAU POS - Chelsy Yesicha (LONTAR: Jurnal Ilmu Komunikasi, 2017)
The research was distributed by the author's interest against Ex Gafatar that occur in Indonesia. Their existence as illegal organization until their expulsion from Earth borneo makes compelling colors for covered by the various media. Each media pack with news of construction in accordance with the ideology they have. So, researchers specializing in the preaching of the Riau Post as local media in spreading the repatriation of Ex Gafatar to Riau. This study used a qualitative approach to discourse analysis models Teun A Van Dijk. Data was collected by interview and documentation. The object of ten research news, consists of nine news from Riau. Informants consisted from chief editor Riau Posâ€™s newspaper. To achieve the validity of the data in this research, researchers used Â triangulation. The results showed: first, Analysis of the discourse, news coverage in newspapers the Riau Post puts a theme raised about the handling of the journey undertaken by the Government of Riau in escorting the repatriation of ex gafatar to Riau. The emphasis on the performance of the apparatus of Government through the promised construction of the Riau Post attempted to grow back the trust of the community to be able to accept back those in neighborhoods with a guarantee from the Government. Second, Representation of the media conducted by the Riau post which uses a constructionist approach is judged in favour to the Government as a form of fostering kepercayaaan Government in dealing with such cases. Without these events, hide impressed the Riau Post tried to suppress the conflict by giving the role of social control to the public.